Perbedaan Peraturan Pembebanan Jembatan RSNI T 02 2005 Dan SNI 1725 2016 - Nurul Aina Syahira (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Elaboration of information regarding differences in bridge loading regulations, especially bridge loading on superstructures between RSNI T 02 2005 and SNI 1725 2016 regulations really needs to be done considering there are still many engineers who don't know and haven't upgraded. Changes to these regulations are based on scientific developments and environmental conditions that continue to change from time to time. The elaboration of the differences in these regulations is carried out to make the engineer aware that the changes that occur must be highly considered and evaluated in order to create a civil building that is strong, sturdy and safe for users.frame and shrinkage, traffic loads, D loads, additional fatigue loads, changes in the calculation of wind and earthquake loads.